A parallel mesh generator based on sequential NETGEN - Yılmaz, Yusuf. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
A parallel tetrahedral mesh generator is developed using the existing sequential NETGEN mesh generator. Mesh generation algorithms developed decompose the geometry or volume mesh into multiple sub-geometries or sub-meshes sequentially on a master node and then create ne volume meshes from those sub-geometries and submeshes in parallel on multiple processors. Three methods are implemented. The rst decomposes the geometry and produces conforming surface sub-meshes from which volume meshes can be generated in parallel. The second and third methods which are re nement based also make use of the CAD geometry information. A scalable mesh migration algorithm that utilizes "owner updates" rule is implemented. Results show that using re nement based methods; a mesh with over a billion volume elements can be generated in under a minute. Our developed software is also distributed freely as open source code at the address http://code.google.com/p/parallel-netgen
Keywords: Numerical grid generation (Numerical analysis)